Pengembangan Media Pembelajaran Interaktif Edpuzzle Mata Pelajaran Teknologi Layanan Jaringan di SMK Pemuda Samarinda - Eltin Parro; Rusdiana Rusdiana; Galih Yudha Saputra; Eko Subastian (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2025)
This study aims to explain the process of developing Edpuzzle learning media and identify the feasibility of media development in learning Network Service Technology. The method used is the ADDIE method for class XI TKJ students at SMK Pemuda Samarinda. Data collection techniques using observation and interviews. The analysis techniques used are skinative analysis techniques and quantitative analysis. The research subjects involved were media experts, material experts and students. The results obtained in this study are very feasible with an average score of 82.26.